Comment on "Corrections to vicinage-effect data fer molecular ions due to foil inhomogeneities" - Eckardt, Juan Cristobal; Lantschner, Gerardo Harald (Comisión Nacional de Energía Atómica; Argentina)
Fil: Eckardt, Juan Cristobal Comisión Nacional de Energía Atómica; Argentina